Suíno como modelo experimental na pesquisa biomédica: valores fisiológicos normais - Gianotti, Giordano Cabral; Beheregaray, Wanessa Krüger; Bianchi, Simone Passos; Mombach, Verônica Santos; Carregaro, Adriano Bonfim; Contesini, Emerson Antonio (Acta Scientiae Veterinariae, 2018)
Background: The use of animals in biomedical research is of great importance. It is fundamental for the development and improvement of new practices and technologies. The selection of the species must take into consideration the practicality of handling and the suitability for the experiment, and it must have low operational costs. Swine are important as an experimental model in several experiment areas, because the functionality of many of their organic systems is developed similarly as it is in humans. Swine are animals that become easily stressed. For that reason, their conditioning is necessary to allow the obtainment of data that is closer to normal parameters. This study aims at reporting the physiological values obtained from awake swine, under normal conditions and minimum stress. Materials, Methods & Results: The animals were maintained under ideal environmental conditions, and they were always handled and conditioned by the same persons. Twenty crossbred swine were evaluated, aged between 60 and 90 days and with a body mass ranging between 17 and 25 kg. The parameters considered were cardiac frequency (FC), emoglobin oxygen saturation (pulse oxymetry – SPO2), respiratory frequency (fR), end tidal carbon dioxide (ETCO2), systolic (PAM), diastolic (PAD) and mean (PAM) arterial pressure and arterial blood gas values – pH, arterial pressure of CO2 (PACO2), arterial pressure of O2 (PAO2), total CO2 (TCO2), base excess (EB), bicarbonate (HCO3) and O2 saturation (SATO2). The experiment was developed in compliance with the Standards of Animal Ethics and Welfare recommended by the National Council on the Control of Animal Experiments and with Law 11.794 of October 2008, being further approved by the Ethics Committee of the Hospital de Clínicas de Porto Alegre. To obtain the FC, fR, ETCO2 and SPO2 values, 20 animal samples were used. FC presented mean values (± standard deviation) of 134 ± 20.67 beats per minute (bpm), showing a maximum value of 180 bpm and a minimum of 103 bpm. The mean fR was 24.5 ± 5.61 breaths per minute (bpm), with a maximum value of 34 bpm and a minimum of 14 bpm, and SPO2 was 96 ± 2.10 %. Moreover, the values obtained in the analysis of exhaled gases showed a ETCO2 at 44.6 ± 5.41 mmHg, with a maximum value of 53 mmHg and minimum value of 34 mmHg. The arterial pressure was obtained from 19 animals, yielding the following values: 135.8 ± 16.29 mmHg for systolic pressure, 81.6 ± 14.10 mmHg for diastolic pressure and 103.3 ± 12.65 mmHg for mean pressure. Samples from 18 animals were used to measure the arterial blood gas. The values obtained were as follows: 7.497 ± 0.019 for Mean pH , 41.7 ± 6.95 mmHg for partial O2 pressure, 90.65 ± 2.5 mmHg for partial CO2 pressure, 32.8 ± 2.18 mmol/L for total CO2, 7.57 ± 1.9 mmol/L for base excess, 31.5 ± 2.12 mmol/L for bicarbonate and 97.55 ± 0.64 for oxygen saturation. Discussion: The animals seemed submissive and able to be conditioned and therefore it was easy to obtain basal values. These data were slightly different from the values obtained in other studies, thus becoming more reliable to be used as parameters in exsperiments employing this species. There seem to be interspecies differences when one intends to make a comparison with human beings. Values such as O2 concentration in arterial blood are normally lower in swine, possibly due to a lower hemoglobin concentration and a higher body temperature in the species. Despite some differences, there are many physiological similarities with human beings, which allows for the conclusion that swine is a great species to be employed in the biomedical research.